PREOPERATIVE AND POSTOPERATIVE TOMOGRAPHIC ASPECTS OF CONDYLE FIXATION AND MANDIBULAR FRACTURE: AN INTEGRATIVE LITERATURE REVIEW: an Integrative Literature Review - Viana, Mayara Rebeca Martins; Santana, Ilan Hudson Gomes de; Menezes Gomes, Victoria Alice; Dutra Felix, Karolayne; Batista Henriques, Maria Eduarda; Pereira Junior, José Marcos; Quintino Miranda, Ítalo; Caetana Pereira, Katia; de Brito Andrade, Arthur Felipe; Elias Silva, Lucas; de Souza Sobral, Andressa; Farias Teixeira, Bárbara Rachelli; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Computed tomography (CT) is crucial for the evaluation of mandibular fractures, especially in complex areas such as the condylar region. Its ability to provide detailed images in multiple planes has improved surgical planning and post-operative monitoring, offering precise information on the location and characteristics of fractures. Objective: This integrative review aims to analyze how tomographic aspects impact surgical planning and postoperative monitoring of condylar and mandibular fractures. The study discusses the advantages and limitations of tomographic techniques in order to understand how they influence the clinical outcome and rehabilitation of patients. Materials and Methods: An integrative literature review was carried out, without the need for submission to the Ethics Committee, in accordance with the guidelines of Normative Instruction No. 510/2016. The search was conducted in databases such as PubMed, Scopus and Web of Science, and expanded with Google Scholar. Results and Discussion: The analysis revealed that cone beam computed tomography (CBCT) provides high-resolution three-dimensional images, which are essential for the accurate assessment of fractures, especially in complex anatomical areas such as the mandibular condyle. Conclusion: Cone beam computed tomography (CBCT) is an indispensable tool for the management of condyle and mandible fractures. Its use in preoperative and post-fixation monitoring facilitates detailed visualization of anatomical structures, improving the precision of surgical interventions and contributing to superior functional and aesthetic results.